EVALUATION OF RHEOGRAPHY OF THE COLON IN IDIOPATHIC MEGARECTOSIGMOIDI IN CHILDREN - N. N. Akhparov; K. E. Khairov; N. B. Аflatonov; K. M. Аkhtarov; M. M. Каlabaeva; A. Zh. Оrazalinov (Креативная хирургия и онкология)
Relevance. Violation of colon function in children remains an important problem in clinical gastroenterology. Until now, there are various approaches to the treatment of the etiology and pathogenesis of chronic constipation and the issue of treatment practice has not been resolved.Purpose of the research. To study blood flow of the sigmoid and rectum wall in idiopathic megarectosigmoid in children.Material and method of the research. The age of patients varies from 3–15 years. The girls were (79%). The results of sigmoid and rectal blood flow in 29 children with constipation and 16 healthy children were studied.Results. Indicators showed that with this pathology, as a rule, there are changes in the intestinal hemodynamics indicating signs of venous congestion, indicating the presence of veniparesis of the vessels of the colon with constipation in children.Conclusion. Summing up the results of the study, we can say that constipation in children is characterized by disorders of hemodynamics of the colon in the form of a decrease in the tone of the vessels, and the depth of the revealed changes in the conditions of the vascular blood flow allows, along with other diagnostic methods, to form indications for surgical intervention and conservative management of patients suffering constipation.